(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Mud crab (Scylla serrata) is one of small scale fisheries commodity that have high economic value and typically associated with good mangrove ecosystem. A habitat degradation will cause a serious impact on the existence of mud crab population. The puropse of this study was to assess the ecological quality of mud crab habitat condition on Bintan Bay’s mangrove ecosystem. Ecological data collection was conducted by using plots line transect for mangrove and the mud carb data collection by using fishermen catch (fisher based survey). The results showed the value of habitat quality index (HQI) of mud crab (Scylla serrata) ranged from 52-82 which mean in the “moderate” category (index value 43-66) and "good" (index value 67-90). It showed that Bintan Bay’s mangrove ecosystems was good enough to support the viability of mud crab. Habitat quality had a linier impact on body weight gain (R2 = 99.78%) and carapace width (R2= 99.21%). This showed that higher the index value of habitat quality, the size of the body weight and carapace width will increases. Keywords: Scylla serrata, habitat quality, ecology, mangroves, and Bintan Bay